Oil storage tank bottom corrosion evaluation using acoustic emission testing - Moura , Carlos André Tavares de; Mainier , Fernando B.; Monteiro , Paulo Roberto Duailibe (Seven Editora, 2023)
The condition of mechanical integrity and the reliability of interconnected storage tanks in the oil export logistics chain in the Brazilian maritime terminals gains in importance in the continuity and operational safety in the coming years. These tanks have large diameters and characteristics that make it difficult to inspect in operation and monitor corrosion damage of the bottom plates. In this scenario, the concern arose with the exhaustion of the installed capacity, which may lead to consequent failures due to loss of containment, compromising not only people, facilities and the environment, but the sustainability of the business itself. Acoustic emission tests were carried out in two oil storage tanks of the marine terminal aiming at the detection and location of regions with corrosive process in the bottom plates. After evaluating the results, it was verified: (1) the relationship between the results found and the expected benefits; (2) the motivations for the use of the technique as an auxiliary tool for monitoring the integrity of the bottom of the tanks in operation; and (3) more assertive planning of shutdowns for general maintenance and internal inspection. DOI:https://doi.org/10.56238/alookdevelopv1-033